Different approaches of clients and consultants to contractors’ qualification and selection - Egemen, Mehmedali; Mohamed, Abdulrezak N. (Journal of Civil Engineering and Management, 2005)
Nowadays, clients are the dominant groups in almost all types of industries. However, the construction industry is unique and consultants, as representatives of clients, are very important figures in this industry as well. By presenting survey findings of 91 clients and 50 consultants, this study reveals clients’ and consultants’ differing expectations of contracting organisations during contractor qualification and selection. The study has clearly confirmed the fact that consultants’ perspectives are rather different and their contractors’ expectations of their clients vary very significantly from the clients themselves. Furthermore, significantly different results were found even among different types of consultants and different categories of clients. Moreover, this study showed that both clients and consultants had high willingness to continue working with the same contractor in possible future works assuming they are satisfied with the previous works. The criteria, which contribute to achieving full client and/or consultant satisfaction and hence lead to possible repetitive works are identified and the results showed the existence of significant difference between clients and consultants perspectives regarding this issue as well. The framework presented within this paper aims to help the contracting organisations to compare and recognise the different approaches and perceptions of both clients and consultants during contractor qualification and selection processes. The contracting organisations in the related sectors will be able to use the framework provided within this study to recognise the overall demand in a more complete and better manner and hence formulate or modify strategies accordingly.Skirtingas klientų ir konsultantų požiūris į rangovo kvalifikaciją ir atrankąSantrauka. Šiandien užsakovai tampa svarbiausia grupe beveik visose pramonės šakose. Tačiau statybos pramonė unikali tuo, kad joje svarbiu asmeniu laikomas dar ir konsultantas, kuris samdomas kaip užsakovo atstovas. Pateikti 91 kliento ir 50 užsakovų apklausos rezultatai, kurie parodė, kaip skiriasi klientų ir užsakovų lūkesčiai dėl rangovų kvalifikacijos ir atrankos. Tyrimas parodė, kad konsultantų reikalavimai rangovams labai skiriasi nuo užsakovo reikalavimų, be to, skirtingi konsultantai ir užsakovai kelia skirtingus reikalavimus rangovams. Tyrimas parodė, kad užsakovai ir klientai yra linkę tęsti bendradarbiavimą su tuo pačiu rangovu tvirtindami, kad yra patenkinti jo ankstesniu darbu. Nustatyti kriterijai, kurių atitikimas lemia užsakovo ir(arba) konsultanto pasirinkimą ir galimybę ateityje laimėti konkursus. Pateikta sistema leidžia konkursuose dalyvaujančioms įmonėms suvokti ir palyginti užsakovų ir konsultantų reikalavimus rangovo atrankos metu. Konkursuose dalyvaujančios įmonės gali naudoti tyrimo rezultatus tam, kad suvoktų užsakovo poreikius, atitinkamai suformuluotų ir pritaikytų savo strategijas.Reikšminiai žodžiai: rangovo kvalifikacija, rangovo atranka, užsakovo lūkesčiai, konsultanto lūkesčiai, užsakovo poreikių patenkinimas, pasikartojantys darbai.First Published Online: 14 Oct 2010